2015
DOI: 10.5483/bmbrep.2015.48.10.015
|View full text |Cite
|
Sign up to set email alerts
|

KSP inhibitor SB743921 induces death of multiple myeloma cells via inhibition of the NF-κB signaling pathway

Abstract: SB743921 is a potent inhibitor of the spindle protein kinesin and is being investigated in ongoing clinical trials for the treatment of myeloma. However, little is known about the molecular events underlying the induction of cell death in multiple myeloma (MM) by SB743921, alone or in combination treatment. Here, we report that SB743921 induces mitochondria-mediated cell death via inhibition of the NF-κB signaling pathway, but does not cause cell cycle arrest in KMS20 MM cells. SB743921-mediated inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Inhibition of the NFκB signal transduction pathway by the kinesin spindle protein inhibitor SB715992 (1 n M concentration) in human multiple myeloma cells results in reduced SOD2 expression and induces cell death in 24 h (335), therefore confirming the role of NFκB in SOD2 stimulation and suggesting a growth-supportive role for the enzyme. Indeed, overexpression of miR146a downregulated SOD2 , reduced human epithelial ovarian cancer cell proliferation, increased apoptosis, and increased sensitivity to chemotherapy (67).…”
Section: Manganese Sod Mnsod Sod2mentioning
confidence: 78%
“…Inhibition of the NFκB signal transduction pathway by the kinesin spindle protein inhibitor SB715992 (1 n M concentration) in human multiple myeloma cells results in reduced SOD2 expression and induces cell death in 24 h (335), therefore confirming the role of NFκB in SOD2 stimulation and suggesting a growth-supportive role for the enzyme. Indeed, overexpression of miR146a downregulated SOD2 , reduced human epithelial ovarian cancer cell proliferation, increased apoptosis, and increased sensitivity to chemotherapy (67).…”
Section: Manganese Sod Mnsod Sod2mentioning
confidence: 78%
“…It has been recognized as a valuable drug target for anticancer therapies and several classes of Eg5 inhibitors have been developed 14 . Monastrol, ispinesib and (+)-S-Trityl-L-cysteine (TriC) are the loop-5 inhibitors and can weaken Eg5 binding to MTs, disrupting Eg5dependent outward force production and inducing the formation of monopolar spindles with unseparated spindle poles [14][15][16][17][18][19] . BRD9876 (BRD) is the "rigor" inhibitor that locks Eg5 in a state with enhanced MT binding, leading to bundling and stabilization of MTs 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have indicated that SB 743921 has shown a wide range of anticancer activities against a variety of malignancies including cervical carcinoma, lymphoma, multiple myeloma, and myeloid leukemia 13,19,20. In this study, we evaluated the potential antitumor effects of SB743921 on breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%